Melatonin-related dysfunction in chronic restraint stress triggers sleep disorders in mice - Xia, Tian-Ji; Wang, Zhi; Jin, Su-Wei; Liu, Xin-Min; Liu, Yong-Guang; Zhang, Shan-Shan; Pan, Rui-Le; Jiang, Ning; Liao, Yong-Hong; Yan, Ming-Zhu; Du, Li-Da; Chang, Qi (Frontiers in Pharmacology, 2023)
Stress may trigger sleep disorders and are also risk factors for depression. The study explored the melatonin-related mechanisms of stress-associated sleep disorders on a mouse model of chronic stress by exploring the alteration in sleep architecture, melatonin, and related small molecule levels, transcription and expression of melatonin-related genes as well as proteins. Mice undergoing chronic restraint stress modeling for 28 days showed body weight loss and reduced locomotor activity. Sleep fragmentation, circadian rhythm disorders, and insomnia exhibited in CRS-treated mice formed sleep disorders. Tryptophan and 5-hydroxytryptamine levels were increased in the hypothalamus, while melatonin level was decreased. The transcription and expression of melatonin receptors were reduced, and circadian rhythm related genes were altered. Expression of downstream effectors to melatonin receptors was also affected. These results identified sleep disorders in a mice model of chronic stress. The alteration of melatonin-related pathways was shown to trigger sleep disorders.